Expectancies in decision making, reinforcement learning, and ventral striatum - Van Der Meer, Matthijs A.; Redish, A. David (Frontiers in Neuroscience, 2010)
Decisions can arise in different ways, such as a gut feeling, doing what worked last time, or planful deliberation. Different decision-making systems are dissociable behaviorally, map onto distinct brain systems, and require different computational demands. For instance, ’model-free’ decision strategies use prediction errors to estimate scalar action values from previous experience, while ’model-based’ strategies leverage internal forward models to generate and evaluate potentially rich outcome expectancies. Animal learning studies indicate that expectancies may arise from different sources, including not only forward models but also Pavlovian associations, and the flexibility with which such representations impact behavior may depend on how they are generated. In the light of these considerations, we review the results of van der Meer and Redish (2009a), who found that ventral striatal neurons that respond to reward delivery can also be activated at other points, notably at a decision point where hippocampal forward representations were also observed. These data suggest the possibility that ventral striatal reward representations contribute to model-based expectancies used in deliberative decision-making.